Processo de adsorção de pigmentos de oleo vegetal com argilas esmectiticas acido-ativadas - Barauna, Osmar Souto (2006)
Orientadores: João Alexandre Ferreira da Rocha Pereira, Cesar Augusto Moraes de Abreu